THE EFFECT OF COMPETENCE, FACILITIES, AND INTERPERSONAL COMMUNICATION ON PATIENT SATISFACTION THROUGH QUALITY OF SERVICE AS INTERVENING VARIABLES IN NATUNA HOSPITAL - Inggerit Paradila Putri; Muammar Khaddafi; Mohamad Gita Indrawan; Indrayani Indrayani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The purpose of this study was to analyze patient satisfaction at the Natuna Hospital. This study uses the variables of competence, facilities and interpersonal communication on the effect of patient satisfaction through service quality. The population in this study were patients at the Natuna General Hospital. While the samples taken in this study were 121 people taken from the population. Data were collected using the questionnaire method, namely by providing a list of questions or questionnaires directly to the respondents. In this study, researchers used SEM-PLS ver.4 processing. In this study, it shows that competence (X1) directly has a positive and significant effect on service quality (Z) with a p-value of 0.023 <0.05, facilities (X2) directly have a positive and significant effect on service quality (Z) with a p-value of 0.000 < 0.05, interpersonal communication (X3) directly has a positive and significant effect on service quality (Z) with a p-value of 0.033 < 0.05 , service quality (Z) directly has a positive and significant effect on patient satisfaction (Y) with a p-value of 0.000 <0.05. In this study, it shows that competence (X1) directly has a positive and significant effect on patient satisfaction (Y) with a p-value of 0.003 < 0.05, facilities (X2) directly have a positive and significant effect on patient satisfaction (Y) with a p-value of 0.001 < 0.05, interpersonal communication (X3) directly has a positive and significant effect on patient satisfaction (Y) with a p-value of 0.000 <0.05, the competence variable (X1) mediates service quality (Z) on patient satisfaction (Y) with a p-value of 0.000 < 0.05, the facility variable (X2) mediates service quality (Z) on patient satisfaction (Y) with a p-value of 0.003 < 0.05, Interpersonal Communication (X3) mediates service quality (Z) on patient satisfaction (Y) with a p-value of 0.001 < 0.05. The R-square value for the Service Quality (Z) variable is 0.680 (68.0%), this value can be explained by factors including X1 (Competence), X2 (Facilities), X3 (Interpersonal Communication), while the remaining 32 ,0% is explained by other variables outside the model.